Genome-Based Analysis of a Sequence Type 1049 Hypervirulent Klebsiella pneumoniae Causing Bacteremic Neck Abscess - Lan, Peng; Zhao, Dongdong; Gu, Jiong; Shi, Qiucheng; Yan, Rushuang; Jiang, Yan; Zhou, Jiancang; Yu, Yunsong (Frontiers in Microbiology, 2021)
Hypervirulent Klebsiella pneumoniae (hvKP) has raised grave concerns in recent years and can cause severe infections with diverse anatomic locations including liver abscess, meningitis, and endophthalmitis. However, there is limited data about neck abscess caused by hvKP. A K. pneumoniae strain Kp_whw was isolated from neck abscess. We characterized the genetic background, virulence determinates of the strain by genomic analysis and dertermined the virulence level by serum resistance assay. Kp_whw belonged to sequence type (ST) 1049 K locus (KL) 5. Kp_whw showed hypermucoviscosity phenotype and was resistant to ampicillin but susceptible to the majority of the other antimicrobial agents. A pLVPK-like virulence plasmid and a chromosomal ICEKp5-like mobile genetic element were carried by Kp_whw, resulting in the risk of dissemination of hypervirulence. The strain exhibited relative higher level of core genome allelic diversity than accessory genome profile, in comparison to hvKP of K1/K2 serotype. Kp_whw was finally demonstrated as virulent as the ST23 K1 serotype hvKP strain NTUH-K2044 in vitro. In conclusion, this work elaborates the genetic background of a clinical hvKP strain with an uncommon ST, reinforcing our understanding of virulence mechanisms of hvKP.